Empowerment Strategy Wawasan Keislaman Umat Melalui Program Safari Subuh Pemkot Palembang - Choiriyah, Choiriyah; Amin, M; Walian, Anang (Wardah, 2024)
This study aims to analyze the Palembang City Government's dawn safari to provide the community with Islamic insight and the concept of prospering mosques. This study's method is descriptive qualitative, directly observing symptoms or events in the field, describing them as data, and drawing conclusions from the data. The findings of this study show that the Palembang City dawn safari program has a positive impact on the development of an Islamic society. Furthermore, regular activities at the mosque can foster a spirit of togetherness and strengthen friendships between communities. Also, the preachers always help Islamic insight people understand the concept of the Islamic religion comprehensively. Thus, we can strengthen the people's economy by communicating with one another about both social and economic development.